Using proteomics, q-PCR and biochemical methods complementing as a multiapproach to elicit the crucial responses of zebrafish liver exposed to neonicotinoid pesticide - SESAL, NÜZHET CENK; GÖKALSIN, BARIŞ; KAYHAN, FİGEN ESİN (My University, 2023)
Pesticides enter the environment through runoff and leaching and this raises public concern about effects on non-target organisms. Imidacloprid (IMI) a synthetic pesticide, has an unstable half-life, metabolized in minutes to weeks in the water. To evaluate the effects of IMI on the zebrafish liver, we conducted proteomic, molecular and biochemical analysis in a multi-level approach, to highlight the complementary features regarding the results of each method. Adult zebrafish were exposed to 60 mg/L IMI for 48 hours and were evaluated using nLC-MS/MS for proteins, q-PCR analysis for expression of cat, gpx, pxr, ache, along with CAT and AChE enzyme activities and GSH and MDA assays. Based on proteomics, the regulation of antioxidant and immune responses, as well as gene transcription were significant processes affected. Apoptosis and ER stress pathways were upregulated and there was a down-regulation of cat and gpx genes. There was also elevated CAT activity and GSH and decreased MDA. Additionally, elevated AChE activity and up regulation of ache expression was observed. The multi-approach results included regulators of antioxidant, xenobiotic response and neuro-protective related proteins (genes and enzymes), which overall reflected harmful effects of IMI. Consequently, this study highlights the effects of IMI on zebrafish liver and reveals new potential biomarkers. In this respect, evaluated outcomes reveal the complementary features emphasizing the importance of studying chemicals using several methods. Our study provides deeper insights for future work in ecotoxicological studies regarding IMI and contribute to existing toxicity literature.
Keywords: Yaşam Bilimleri; Hidrobiyoloji; Moleküler Biyoloji ve Genetik; Temel Bilimler; Life Sciences; Hydrobiology; Molecular Biology and Genetics; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Doğa Bilimleri Genel; Biyoloji ve Biyokimya; ÇOK DİSİPLİNLİ BİLİMLER; BİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); NATURAL SCIENCES, GENERAL; BIOLOGY & BIOCHEMISTRY; MOLECULAR BIOLOGY & GENETICS; MULTIDISCIPLINARY SCIENCES; BIOLOGY; Moleküler Biyoloji; Multidisipliner; Molecular Biology; Multidisciplinary